Evaluating the global efficiency of teachers through a multi-criteria approach - Marcenaro-Gutiérrez, Óscar David; Luque-Gallego, Mariano; Ruiz, Ana Belen (Elsevier, 2020)
Improving the quality of education is one of the main objectives for governments, given that it plays an essential role in providing well-being to the population. In this regard, the efficiency of teachers may be a key issue to improve the students' academic performance and learning achievement. Specifically, in this paper, we analyse the efficiency of teachers from a multi-criteria optimization perspective. The purpose is to detect the most efficient teachers to gain knowledge about the characteristics of their teaching context, which contribute to increase the education performance of the students. To this aim, data from TIMSS and PIRLS 2011 for fourth- grade reading, mathematics and science teachers in Spain have been used. Three synthetic indexes gathering these data are calculated: a weak index allowing full compensation among the variables, a strong index in- forming about the worst variable value (no compensation scheme) and a synthetic index representing a different degree of compensation of the two formers. These indexes are built using aspiration and reservation levels for each variable. This allows us to include desirable ranges of values to be achieved by the variables in the study of the teachers' efficiency. With this, it is possible to know if the teachers are performing better, within or worse than the desired limits, and to rank the teachers according to their efficiency. The analysis carried out has contributed to have a better understanding of the policies to be followed in order to promote efficiency in teaching.
Keywords: Optimización; Profesores - Formación profesional; Efficiency; Teachers; Synthetic index; Primary education